KEPENTINGAN INDONESIA MERATIFIKASI PROTOKOL NAGOYA 2013 - Islami, Tegar; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study describes the policy nagoya Indonesia ratified the protocol, this protocol governing access to genetic resources and equitable sharing of benefits arising from the balanced utilization on biodiversity convention, the Nagoya Protocol is important for Indonesia because this protocol is an instrument to prevent the theft of genetic resources (biopiracy), Indonesia is a country that has a wealth of genetic resources are very large. because of the wealth of Genetic Resources, Indonesia dubbed 'megadiversity'. Genetic Resource Wealth requires good management and protection, corporations from developed countries often take on Genetic Resources without the permission. For Indonesia Natural Resources is not only economic and technical issues, but rather the reflection of the demands of the cultural issues and foreign relations are dynamic, so it is important to be managed diplomatically. Protection of Natural Resources is expected to bring in substantial benefits to the people of Indonesia where the statement Indonesian vice president Boediono that this will bring great economic development for the people of Indonesia because Indonesia is a giant social laboratory, Indonesia has ratified the Nagoya Protocol by issuing Law No. 11 in 2013 on the Ratification of the Nagoya Protocol on access to Genetic Resources and Benefit Sharing Fair and Balanced Arising From Utilization Keyword : Foreign Policy , Nagoya Protocol , Biopiracy , Megadiversity, Genetic Resources